(untitled) (Academia Journal of Medicine, 2023)
Photodynamic Therapy: A Revolutionary Approach in Dentistry. Acad J Med 2023; 6(1): 8-13. Photodynamic therapy (PDT) is a promising adjunctive approach in dentistry. This abstract reviews the current status of PDT in dental applications, focusing on its antimicrobial efficacy, wound healing properties, and potential for periodontal and endodontic therapies. Highlighting the clinical implications and future directions, it emphasizes PDT’s non invasiveness and low cytotoxicity. Despite challenges, PDT demonstrates potential as a valuable tool in managing oral infections and promoting tissue healing, presenting opportunities for further research and clinical utilization.